Unhealthy diets increase the likelihood of being overweight or obese among African migrant students in China, but not among African non-migrant students: a cross-sectional study - Awudi, Doris Abra; Walker, Anita Nyarkoa; Weeto, Mary Makhala; Priddy, Christiana Babymay; Akan, Otobong Donald; Baduweh, Cynthia Anuseh; Arthur, Bella Abigail; Yakubu, Salimata; Bafei, Solim Essomandan Clémence; Olagunju, Timothy Mobolaji; Zaitoun, Margaret; Zhong, Yuxia; et al. (Frontiers in Nutrition, 2024)
Background: Non-communicable diseases (NCDs) impacts are disproportionately felt by immigrants from low-to medium-income countries (LMIC), partly due to the food they eat. To thrive in their new environment, migrants either omit or consume certain food items, which could lead to nutritional deficits. As a result, most migrants experience more NCDs than their compatriots in their native countries. We therefore evaluated the difference in the dietary habits, quality, and the influencing factors of overweight or obesity amongst African migrant students in Nanjing (China) and nonmigrant students in Africa using cross-sectional data.The researchers used the food frequency questionnaire and the global diet quality score metrics to assess the food intake and quality, respectively. Then, cross-tabulation was employed to explore the differences between the groups in meal skipping, eating habits, and diet quality.Lastly, the factors associated with overweight or obesity were assessed with binary logistic regression stratified by African students in Nanjing and students in their native countries.Results: About 678 responses were received, mainly between 18 to 25 years (46.7 %) and 26 to 36 years (45.4 %). The majority of them were international students, 52.3%. The nonmigrant African students' diets lacked citrus fruits (22.2%), deep orange fruits (15.4%), deep orange vegetables (18%), cruciferous vegetables (24.6%), and dark leafy vegetables (26.5%). While the African migrant students consumed more high-fat dairy (50.7%), processed meats (23.9%), sweets and ice creams (51.3%), sugar-sweetened beverages (40.5%), and juice (61.5%), p < 0.001. Furthermore, consuming late-night meals constantly (Exp (B) = 39.607, p = 0.049), eating twice a day (Exp (B) = 6.527, p=0.036), red meat (Exp (B) = 29.287, p=0.001), processed meats (Exp (B) = 719.979, p=0.0011), refined grains and baked foods (Exp (B) = 15.752, p=0.013), and sweets and ice cream (Exp (B) = 193.633, p=0.006) were inducing overweight or obesity factors among only African migrant students. Conclusion: In conclusion, controlling the what (western diet and nature of late-night meals) and the when of eating can drastically reduce their influence on obesogenic condition formation in African migrant students in China and elsewhere.